Maturing Usability Quality in Software, Interaction and Value - Law, Effie Lai-Chong; Hvannberg, Ebba; Cockton, Gilbert (Human-Computer Interaction Series, 2008)
"Maturing Usability" provides an understanding of how current research and practice has contributed towards improving quality from the perspectives of software features, interaction experiences and achieved value. Divided into three parts, 'Quality in Software' looks at how using development tools can enhance usability of a system, and how methods and models can be integrated into the development process to produce effective user interfaces. 'Quality in Interaction' addresses theoretical frameworks on the nature of interactions; techniques and metrics for evaluation interaction quality; and the transfer of concepts and methods from research to practice. Finally, 'Quality in Value' assesses the impact that a system has in the real world, focusing on increasing the value of usability practice for software development and on increasing value for the users. A balance between theoretical and empirical approaches is maintained throughout, and all those interested in exploring usability and emerging usage qualities in human-computer interaction will find this a very useful book.